Daya Gabung Galur-galur Jagung Berkualitas Protein Tinggi - Azrai, Muhammad; Mejaya, Made Jana; Aswidinnoor, Hajrial (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2014)
Quality Protein Maize (QPM) is a special maize functioning as source of carbohydrate and protein, which contain protein components lysine and tryptophan higher than that of normal maize. Experiment was carried out to evaluate the combining abilities of inbred lines introgressed with opaque-2 mutant gene and their hybrid performances on grain yield and other agronomic characters. Genotype test consisted of eight lines, eight testers, sixty four hybrid crosses between lines x tester and four check varieties. The experiment was arranged in a randomized complete block design, with two replications, on the lowland in Walenreng (Bone) and on dry land in Bajeng (Gowa). Variance analyses were done following the line x tester model. Results showed that the effect of genotype x location interactions were significant for ear weight and yield characters. The grain yields of three lines showed positive and significant general combining ability those were Nei9008+o2-09 (L1), Nei9008+o2-14 (L3) and Nei9008 + o2-27 (L7), but for the tester was only MR10+o2-31 (T7). Another eight crosses were showing significant effect for specific combining ability, but only combination of Nei9008+o2-09 and o2+MR10-31 lines was significantly superior to all check hybrids.